118. Appearance of muscle motor evoked potentials after untethering of the spinal cord. Issue 4 (April 2016) - Nuti, A.; Arcaro, C.; Tramontano, V.; Basaldella, F.; Squintani, G.; Sala, F.
Abstract : To describe the intraoperative appearance or improvement of lower extremity muscle motor evoked potentials (mMEPs) during tethered cord surgery for spinal dysraphisms. A 3-year old male child with dermal sinus and dorsal lipoma, and a 30-year old male with a sacral lipoma were operated on for untethering the cord under Intra-operative neurophysiological monitoring (IONM) surveillance. The IONM protocol included: Transcranially elicited mMEPs, Posterior Tibial Nerve Somatosensory Evoked Potentials (TPN-SSEPs), recording of the bulbo-cavernous reflex (BCR), and mapping of the cauda equina. Recording electrodes were inserted bilaterally in the Anterior Tibialis (AT), Gastrocnemius (GR), Abductor Hallucis Brevis (AHB), and the anal sphincter muscles (ASM). In the child, at baseline only the right AHB mMEP was elicitable at 200 mA. Following cord untethering a progressive reappareance of the left GR, AT and AHB mMEP was observed starting about 10 min. after the cord was completely untethered. In the adult case, all mMEPs were present at baselines but, in spite of unchanged stimulation intensity, after untethering the cord mMEP amplitude increased significantly in the left AHB and GR muscles. The anesthesiological regimen was stable throughout the procedures. IONM may detect acute improvement of mMEPs during cord untethering, possibly due to better oxidative metabolism in the conus.